Antioxidant and Antimicrobial Activity of Bunias orientalis L. and Scorzonera hispanica L. Ethanol Extracts - Vergun, Olena; Kačániová, Miroslava; Rakhmetov, Dzhamal; Shymanska, Oksana; Bondarchuk, Oleksandr; Brindza, Ján; Ivanišová, Eva (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The current study was aimed to evaluate an accumulation in plant raw material of Bunias orientalis L. and Scorzonera hispanica L. the total content of phenolic compounds, phenolic acids, flavonoids, antioxidant activity (by DPPH-method) and reducing power of alcoholic extracts. Raw of investigated plants collected from experimental collections of M.M. Gryshko National Botanical Garden of the NAS of Ukraine (Kyiv) and dried for next investigation. Obtained results showed that total content of polyphenols in the above-ground parts of B. orientalis extracts was 52.88 mg g-1 GAE (gallic acid equivalent), phenolic acids – 11.29 mg g-1 CAE (caffeic acid equivalent), flavonoids – 39.91 mg g-1 QE (quercetin equivalent), antioxidant activity – 8.94 mg g-1 TE (Trolox equivalent) and reducing power of extracts – 184.59 mg g-1 TE (Trolox equivalent). Total content of polyphenols in the above-ground parts of S. hispanica plants was 60.16 mg g-1 GAE, phenolic acids – 20.71 mg g-1 CAE, flavonoids – 36.24 mg g-1 QE, antioxidant activity – 5.35 mg g-1 TE and reducing power of extracts – 125.40 mg g-1 TE. Also, total content of polyphenols in the roots of B. orientalis extracts was 9.75 mg g-1 GAE, phenolic acids – 1.73 mg g-1 CAE and reducing power of extracts – 138.70 mg g-1 TE. Root extracts of S. hispanica had total content of polyphenols of 10.87 mg g-1 GAE, phenolic acids – 2.62 mg g-1 CAE and reducing power of extracts – 110.96 mg g-1 TE. Flavonoids and antioxidant activity in the root extracts of both species weren’t determined. The antimicrobial activity of alcoholic extracts of two investigated species was tested against 8 microorganisms by disc diffusion method. It was found that higher activity against microbial strains had alcoholic extracts of B. orientalis roots.